Colonial Fear and Politicisation of South Lebanese Shia Immigrants in Senegal in the Intrawar Period - (:unkn) unknown (My University, 2018)
This article studies the politicisation of Shia Muslim immigrants from South Lebanon or Jabal ‘Âmil who settled in Senegal, more specifically in Dakar, which was the main gateway to French West Africa throughout the colonial period. It shows the extensive nationalist political networks organised by immigrants fully involved in the debates and controversies of the Nahda and the cleavages running through the nebulous Syrian nationalist movement during the interwar period. At the same time, a new generation of propagandists – who were unyielding in their desire for independence and revolutionary in their definition of the Syrian national community – were increasingly critical of the contradictions of the French Mandate for Syria and the Lebanon. Thus, these networks offered immigrants the possibility to protest French imperialism from its margins. Behind a religious vocabulary and the fear of pan-Islamism spreading into Muslim-majority black Africa, colonial administrators were most fearful of French West Africa becoming part of a Muslim world that had been increasingly self-aware since the start of the century. They were convinced of Islam’s subversive power in Africans protesting the colonial order.
Keywords: African Research